Modified COVID-19 Mortality Scoring as a Mortality Prognostic in COVID-19 Patients - Rahmadani Puji Lestari; Benedictus Hangga Harinawantara; Khoironi Rachmad Damarjati; Purwadi Sujalmo (Rumah Sakit Akademik Universitas Gadjah Mada, 2022)
Background: The number of patients infected with COVID-19 was increasing. The COVID-19 clinical presentation varies from asymptomatic, mild, moderate, severe, and critical. Mortality rates increase with morbidity and disease severity. This study aimed to develop a prognostic intrahospital mortality scoring named